'Weapons from their land': arming strategies and practices among West African-born soldiers in early nineteenth-century Bahia and Cuba. (3rd July 2018) - Barcia, Manuel
ABSTRACT: This article addresses the essential issue of weaponry and war paraphernalia used by West African men and women in Bahia and Cuba throughout the first half of the nineteenth century. It argues that it was due to the similarities existing between their African and American environments that they were able to reproduce the ways in which they had acquired the weapons necessary to undertake their military actions. Moving away from the concept of slave revolt, and considering these movements as actions of war, also allows for a more in-depth examination of the question of weaponry. Were the weapons they used African or Western? How were West African practices associated with the arming of military forces reproduced in the new setting provided by plantation societies in Bahia and Cuba? These, among other questions, are addressed in this article.